1998
DOI: 10.3810/psm.1998.08.1101
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondritis Dissecans of the Knee

Abstract: Osteochondritis dissecans (OCD) should be considered in young, active patients who have generalized or anterior knee pain. A careful physical exam includes a Wilson test, thigh girth measurements, diagnostic tunnel view radiographs, and other imaging studies as needed for grading and prognosis. Two case reports demonstrate the signs and symptoms of OCD. Treatment by primary care physicians with sports medicine training may be conservative if lesions are medial and in situ and if patients are not skeletally mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Mechanical symptoms such as locking or catching may signify the presence of a loose body or advanced disease [3••, 13,20,29]. Thigh atrophy has also been reported as a reliable late finding, with OCD secondary to thigh disuse [6,25,30]. On examination, 23 %-44 % of patients may have a joint effusion, and between 40 % and 70 % can have point tenderness over the affected femoral condyle [11,14,27].…”
Section: Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical symptoms such as locking or catching may signify the presence of a loose body or advanced disease [3••, 13,20,29]. Thigh atrophy has also been reported as a reliable late finding, with OCD secondary to thigh disuse [6,25,30]. On examination, 23 %-44 % of patients may have a joint effusion, and between 40 % and 70 % can have point tenderness over the affected femoral condyle [11,14,27].…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…A similar phenomenon can be elicited on physical examination with the Wilson test [31], in which the examiner extends the knee from 90°to 30°against resistance while internally rotating the tibia. The test is considered positive when symptoms are reproduced by internal rotation and relieved by external rotation [6,7]. While the sensitivity and specificity for this test are unknown, previous authors have anecdotally found it to be nondiagnostic [32].…”
Section: Clinical Evaluationmentioning
confidence: 99%